Análise da gestão integrada dos resíduos sólidos no munícipio de Beberibe-CE - Fonseca, Letícia Monteiro da (2021)
Population growth tied to economic development has altered society's consumption patterns leading to the deliberate production of solid waste, which is currently one of the main threats to public health and environmental balance. In 2010, federal Law No. 12,305 was published, which establishes the National Solid Waste Policy (PNRS) with the purpose of directing actions for the correct control and management of waste in the country. In the same year, it was regulated by Federal Decree No. 7,404. Thus, the PNRS assigns to the municipalities and the Federal District the competence for the integrated management of solid waste generated in their territories. In this sense, the study consists of analyzing the integrated management of solid waste in the municipality of Beberibe - CE, highlighting the laws at the national, state and municipal levels relevant to the subject. Thus, bibliographic research, photographic survey and visits to municipal agencies were carried out to verify the control and management of solid waste, the situation of the intermunicipal consortium in which the federative is integrant and the place of final disposal of these wastes. The main results obtained were: dump as a method of final disposal; presence of recyclable and reusable materials waste pickers in the area of the dump; absence of educational campaigns and selective collection system and reports of difficulties of the consortium in consolidating actions. Thus, in the municipality of Beberibe, the integrated management of solid waste can be considered inefficient, because only basic activities are carried out in the management of waste, such as collection, transportation and final disposal, which is environmentally inadequate and is therefore in disagreement with current regulations.